Chronic Administration of Tadalafil Improves the Symptoms of Patients with Amicrobic MAGI: An Open Study. (30th March 2017) - La Vignera, Sandro; Condorelli, Rosita A.; Mongioi, Laura M.; Calogero, Aldo E.
Abstract : Aim of this study was to evaluate the effects of pharmacological treatment with Tadalafil 5 mg daily on symptoms and quality of sperm parameters in selected patients with amicrobic MAGI (male accessory gland inflammation). 120 patients with amicrobic MAGI (mean age 27.0 ± 6.0 years) with mild-moderate ED (erectile dysfunction) according to IIEF-5 (International Index of Erectile Function 5 Items) scores underwent pharmacological treatment with Tadalafil 5 mg daily for six months. Before and after treatment these patients were evaluated through IIEF-5, semen analysis (according to WHO Criteria, 2010), SI-MAGI (Structured Interview about Male Accessory Gland Inflammation), and ultrasound evaluation. Patients with PVE (prostate-vesciculo-epididymitis) showed a significant increase in the percentage of spermatozoa with total (16.0 ± 8.0 versus 30.0 ± 6.0%) and progressive motility (8.00 ± 10.0 versus 25.0 ± 6.00%). It was a significant reduction of the number of patients with complicated ultrasound forms (30.0 versus 52.0) and a significant increase of the number of patients with uncomplicated ultrasound form (90.0 versus 68.0). Finally, there was a significant reduction in the percentage of patients with alterations of sexual function different from DE, such as premature ejaculation (4.00 versus 8.00%), painful ejaculation (4.00 versus 10.0%), delayed ejaculation (12.50 versus 8.00%), and decreased libido (10.0 versus 25.0%).